Oxyropsis ephippia, a New Hypoptopomatine Catfish (Siluriformes: Loricariidae) from Guyana - Aquino, Adriana E.; Pérez, Mark H. Sabaj (Zootaxa, 2016)
Oxyropsis ephippia, a new species of loricariid catfish in the subfamily Hypoptopomatinae, is described from the Essequibo and Branco basins, Guyana. Based on the presence of a keel-like row of relatively enlarged odontodes on trunk median plates immediately above the lateral line canal, the new species is assigned to the genus Oxyropsis Eigenmann & Eigenmann 1889. It can be distinguished from its congeners by having the keel-like row on each median plate dominated by a single odontode (one closest to the posterior margin of the plate) conspicuously larger than preceding ones, and by having the sides of the trunk below the median series (approximately between median plates 7 to 12) shielded only by plates of the midventral series, with the exclusion of plates from the ventral series. The report of O. ephippia from the Essequibo is the first record of the genus in a river system that drains the north-central portion of the Guiana Shield into the Atlantic Ocean.